Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2010
DOI: 10.1123/ijsnem.20.4.275
|View full text |Cite
|
Sign up to set email alerts
|

Aerobic Exercise Training-Induced Decrease in Plasma Visfatin and Insulin Resistance in Obese Female Adolescents

Abstract: The purpose of this study was to assess differences in the levels of plasma visfatin among female adolescents and changes in plasma visfatin and insulin resistance in obese female adolescents after 12 wk of aerobic exercise training. Twenty normal-weight female students (body-mass index [BMI] < 22.9 kg/m² and body fat ≤ 29.9) and 18 obese female students (BMI ≥ 25 kg/ m² and body fat ≥ 30%) participated in this study. Eleven obese students were assigned to an exercise group and completed a 12-wk aerobic exerci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
54
3
15

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(73 citation statements)
references
References 32 publications
(55 reference statements)
1
54
3
15
Order By: Relevance
“…Similarly, Brema et al (2008) found decreased visfatin levels, in addition to waist circumference, in 30 15-year-old obese participants with type 2 diabetes before and after 12 weeks of aerobic training performed at 75% of maximum aerobic power for one hour utilizing four sessions weekly (35). Lee et al (2010) too observed that 12 weeks of aerobic training resulted in reduced visfatin concentrations in obese females (10).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Similarly, Brema et al (2008) found decreased visfatin levels, in addition to waist circumference, in 30 15-year-old obese participants with type 2 diabetes before and after 12 weeks of aerobic training performed at 75% of maximum aerobic power for one hour utilizing four sessions weekly (35). Lee et al (2010) too observed that 12 weeks of aerobic training resulted in reduced visfatin concentrations in obese females (10).…”
Section: Discussionmentioning
confidence: 99%
“…the role of visfatin in the development of overweightness and obesity arises from those studies that demonstrate increased visfatin concentrations in overweight and obese individuals (10,11). In addition, these elevated visfatin concentrations and its gene expression in fat cells in obese individuals provides convincing evidence of the relationship of visfatin with visceral fat mass and body mass index (12).…”
Section: Introductionmentioning
confidence: 92%
See 2 more Smart Citations
“…41 Lee et al evaluated the influence of aerobic exercise over 3 months of training on plasma visfatin levels and showed a significant reduction in the plasma levels of visfatin and insulin resistance. 42 In a study on 50 professional female basketball and handball players, it was observed that plasma adiponectin levels decreased after 2 hours of aerobic exercise. 43 Haus et al also reported that aerobic exercise reduced the level of plasma visfatin followed by improved glucose tolerance.…”
Section: Findings On the Effects Of Aerobic Exercise On Serum Visfatimentioning
confidence: 99%